SOSIALISASI PENYAKIT AKIBAT KERJA DALAM UPAYA MENINGKATKAN KESEHATAN KERJA DI PT CHEMKO KABUPATEN KARAWANG - Muhidin, Muhidin; Darmawan, Wendi; Yuliana, Chaerani Tri; Jumaedi, Jumaedi; Widhiantika, Wieke (LP2M STP Mataram, 2024)
The program Work-Related Disease Awareness in an Effort to Improve Occupational Health at PT Chemko, Karawang aims to raise employees' awareness and knowledge about the risks of work-related diseases and how to prevent them. In the chemical industry environment, workers are exposed to various health risks that can lead to long-term health issues if proper preventive measures are not taken. This program includes several stages, such as seminars, training on the use of personal protective equipment (PPE), work accident response simulations, and monitoring the implementation of occupational health protocols. The results show a significant increase in workers' understanding of the importance of workplace safety and compliance with PPE usage. Additionally, strong support from management and company policies plays a vital role in the success of this program. However, regular monitoring is still necessary to ensure long-term compliance with safety protocols. With the implementation of this program, the incidence of work-related diseases is expected to decrease, leading to a healthier and safer work environment